Optimization of sodium hydroxide pretreatment and enzymatic saccharification of spent rubberwood sawdust for glucose production - Siti Aminah Mohd Hassan (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2014)
The study was conducted to improve the added value of mushroom spent medium as an alternative glucose source to the current expensive sugar crops and starchy products.